Ullrich scleroatonic muscular dystrophy is caused by recessive mutations in collagen type VI - Camacho Vanegas, Olga (The National Academy of Sciences, 2001)
Ullrich syndrome is a recessive congenital muscular dystrophy affecting connective tissue and muscle. The molecular basis is unknown. Reverse transcription–PCR amplification performed on RNA extracted from fibroblasts or muscle of three Ullrich patients followed by heteroduplex analysis displayed heteroduplexes in one of the three genes coding for collagen type VI (COL6). In patient A, we detected a homozygous insertion of a C leading to a premature termination codon in the triple-helical domain of COL6A2 mRNA. Both healthy consanguineous parents were carriers. In patient B, we found a deletion of 28 nucleotides because of an A → G substitution at nucleotide −2 of intron 17 causing the activation of a cryptic acceptor site inside exon 18. The second mutation was an exon skipping because of a G → A substitution at nucleotide −1 of intron 23. Both mutations are present in an affected brother. The first mutation is also present in the healthy mother, whereas the second mutation is carried by their healthy father. In patient C, we found only one mutation so far—the same deletion of 28 nucleotides found in patient B. In this case, it was a de novo mutation, as it is absent in her parents. mRNA and protein analysis of patient B showed very low amounts of COL6A2 mRNA and of COL6. A near total absence of COL6 was demonstrated by immunofluorescence in fibroblasts and muscle. Our results demonstrate that Ullrich syndrome is caused by recessive mutations leading to a severe reduction of COL6.